2016
DOI: 10.1007/s00240-016-0882-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a distinct gut microbiome in kidney stone formers compared to non-stone formers

Abstract: The trillions of microbes that colonize our adult intestine are referred to as the gut microbiome (GMB). Functionally it behaves as a metabolic organ that communicates with, and complements, our own human metabolic apparatus. While the relationship between the GMB and kidney stone disease (KSD) has not been investigated, dysbiosis of the GMB has been associated with diabetes, obesity and cardiovascular disease. In this pilot study we sought to identify unique changes in the GMB of kidney stone patients compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
121
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 32 publications
12
121
0
Order By: Relevance
“…34 These prior studies, however, identified differences in the abundance of other bacteria such as Eubacterium and reported that patients with kidney stones had an lower overall diversity of the gut microbiome. 3,4 This lower diversity is consistent with the loss of microbiota diversity reported in other diseases, such as asthma. 35 It is likely that multiple organisms would mediate the association between antibiotics and nephrolithiasis because intestinal microbes exist as a community of organisms, with the metabolic functions of one species affecting growth of others.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…34 These prior studies, however, identified differences in the abundance of other bacteria such as Eubacterium and reported that patients with kidney stones had an lower overall diversity of the gut microbiome. 3,4 This lower diversity is consistent with the loss of microbiota diversity reported in other diseases, such as asthma. 35 It is likely that multiple organisms would mediate the association between antibiotics and nephrolithiasis because intestinal microbes exist as a community of organisms, with the metabolic functions of one species affecting growth of others.…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies reported differences in the composition of the intestinal microbiome between patients with and without nephrolithiasis. 3,4 Additionally, multidrug resistant nonurease-producing bacteria have been isolated from calcium-based kidney stones extracted from patients without urinary tract infection (UTI), suggesting a role for selective pressure on the urinary microbiome in kidney stone formation. 5 However, despite the well established effect that antibiotics have on the microbiome, it remains unclear whether antibiotics are a risk factor for nephrolithiasis.…”
mentioning
confidence: 99%
“…A recent study has identified distinct differences in the gut microbiome of kidney stone patients compared to patients without stones [3]. Fecal and urine samples collected from both groups of patients revealed 178 genera, of which the five most abundant enterotypes, or distinct bacterial communities, within each group made up greater than 50% of the bacterial abundance identified.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney stone formation is a common disease with a high morbidity (1). Kidney stones can lead to the development of severe diseases such as hydronephrosis, renal function impairment or insufficiency if active treatment is not undertaken.…”
Section: Introductionmentioning
confidence: 99%